ENGINEERED MODULAR RECOMBINANT TRANSPORTERS: APPLICATION OF NEW PLATFORM FOR TARGETED RADIOTHERAPEUTIC AGENTS TO α-PARTICLE EMITTING (211)At - Rosenkranz, Andrey A. (2008)
PURPOSE: To generate and evaluate a modular recombinant transporter (MRT) for targeting (211)At to cancer cells overexpressing the epidermal growth factor receptor (EGFR). METHODS AND MATERIALS: The MRT was produced with four functional modules: (1) human epidermal growth factor as the internalizable ligand, (2) the optimized nuclear localization sequence of simian vacuolating virus 40 (SV40) large T-antigen, (3) a translocation domain of diphtheria toxin as an endosomolytic module, and (4) the Escherichia coli hemoglobin-like protein (HMP) as a carrier module. MRT was labeled using N-succinimidyl 3-[(211)At]astato-5-guanidinomethylbenzoate (SAGMB), its (125)I analogue SGMIB, or with (131)I using Iodogen. Binding, internalization, and clonogenic assays were performed with EGFR-expressing A431, D247 MG, and U87MG.wtEGFR human cancer cell lines. RESULTS: The affinity of SGMIB-MRT binding to A431 cells, determined by Scatchard analysis, was 22 nM, comparable to that measured before labeling. The binding of SGMIB-MRT and its internalization by A431 cancer cells was 96% and 99% EGFR specific, respectively. Paired label assays demonstrated that compared with Iodogen-labeled MRT, SGMIB-MRT and SAGMB-MRT exhibited more than threefold greater peak levels and durations of intracellular retention of activity. SAGMB-MRT was 10–20 times more cytotoxic than [(211)At]astatide for all three cell lines. CONCLUSION: The results of this study have demonstrated the initial proof of principle for the MRT approach for designing targeted α-particle emitting radiotherapeutic agents. The high cytotoxicity of SAGMB-MRT for cancer cells overexpressing EGFR suggests that this (211)At-labeled conjugate has promise for the treatment of malignancies, such as glioma, which overexpress this receptor.